Uso de diferentes crioprotetores em diluentes para sêmen ovino congelado - Tonieto, Rafael Adolfo (2008)
The low pregnancy rates obtained with artificial insemination using frozen ram semen make its routine use unfeasible. As the cryopreservation process causes injuries in the sperm cells, the development of extenders that include state-of-the art cryoprotectant solutions is justified. This study tested the inclusion of low density lipoprotein (LDL) and trehalose in extenders for freezing ram semen, by evaluating parameters of post-thawing semen quality. In the first experiment, 3 treatments were compared: Tris including 20% egg yolk and 5% glycerol (T1); Tris including 10 mM trehalose (T2); and T1 including 50 mM trehalose (T3). Sperm motility did not differ across treatments (P > 0.05), but T2 presented higher proportion of sperm cells having membrane integrity (P < 0.05). In the second experiment, 4 treatments were compared: Tris including 20% egg yolk (T1); T1 including 5% glycerol (T2); T1 including 100 mM trehalose (T3); and t1 including 100 mM trehalose and 5% glycerol (T4). Sperm motility and membrane integrity were higher for T2, T3 and T4 than for T1 (P < 0.05), but acrossome integrity did not differ among treatments (P > 0.05). In the third experiment, four treatments were compared: Tris including 20% egg yolk and 100 mM trehalose; and T1 with the replacement of egg yolk by LDL including 5% glycerol (T2); 100 mM trehalose (T3); and 100 mM trehalose and 5% glycerol (T4). Sperm motility and membrane integrity were higher for T2 and T3 than for the other treatments (P < 0.05), but there was no further difference among the LDL treatments (P > 0.05). Acrossome integrity did not differ across treatments (P > 0.05). Therefore, the inclusion of LDL and trehalose as cryoprotectants in extenders for frozen ram semen was associated with improvement in post-thawing sperm motility and membrane integrity.